Nanomaterials in the environment: Behavior, fate, bioavailability, and effects—An updated review. (16th July 2018) - Lead, Jamie R.; Batley, Graeme E.; Alvarez, Pedro J. J.; Croteau, Marie‐Noële; Handy, Richard D.; McLaughlin, Michael J.; Judy, Jonathan D.; Schirmer, Kristin
Abstract: The present review covers developments in studies of nanomaterials (NMs) in the environment since our much cited review in 2008. We discuss novel insights into fate and behavior, metrology, transformations, bioavailability, toxicity mechanisms, and environmental impacts, with a focus on terrestrial and aquatic systems. Overall, the findings were that: 1) despite substantial developments, critical gaps remain, in large part due to the lack of analytical, modeling, and field capabilities, and also due to the breadth and complexity of the area; 2) a key knowledge gap is the lack of data on environmental concentrations and dosimetry generally; 3) substantial evidence shows that there are nanospecific effects (different from the effects of both ions and larger particles) on the environment in terms of fate, bioavailability, and toxicity, but this is not consistent for all NMs, species, and relevant processes; 4) a paradigm is emerging that NMs are less toxic than equivalent dissolved materials but more toxic than the corresponding bulk materials; and 5) translation of incompletely understood science into regulation and policy continues to be challenging. There is a developing consensus that NMs may pose a relatively low environmental risk, but because of uncertainty and lack of data in many areas, definitive conclusions cannot be drawn. In addition, this emerging consensus will likely change rapidly with qualitative changes in the technology and increased future discharges. Environ Toxicol Chem 2018;37:2029–2063. © 2018 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.